Intravitreal Clindamycin and Dexamethasone Combined with Systemic Oral Antitoxoplasma Therapy versus Intravitreal Therapy Alone in the Management of Toxoplasma Retinochoroiditis: A Retrospective Study - Ashraf Bor’i; Ashraf Mahrous; Mahmoud A. Al-Aswad; Haitham Y. Al-Nashar; Waled M. Nada; Mostafa Wagih; Ahmed M. B. Awad; Wael M. El-Haig (Journal of Ophthalmology)
Purpose. To compare clinical outcome of IVCD combined with oral therapy with IVCD alone in patients with toxoplasmic retinochoroiditis. Patients and Methods. Thirty eyes were reviewed. Two equal groups were identified (15 eyes each). Clinical outcome measures were resolution of active inflammation, changes in BCVA and CMT, adverse drug reactions, and rate of recurrence. Results. Mean baseline of BCVA 1.08 ± 0.17 and 1.03 ± 0.15 improved to 0.64 ± 0.18 and 0.69 ± 0.17 at the end of follow-up in group I and II, respectively. No statistically significant difference was observed. CMT was 392.6 ± 33.16 μm and 397.3 ± 14.6 μm significantly decreased to 314.7 ± 4.43 μm and 319.6 ± 7.8 μm. Resolution of acute inflammation was achieved in all cases in both groups. There were no recurrent cases in group I, and only one out of 15 (6.7%) in group II. No ocular or systemic adverse events were recorded. Conclusion. IVCD is an effective route of treatment for active toxoplasmic retinochoroiditis that can be used solely without the need to use systemic medications..